2011
DOI: 10.4103/1119-3077.84028
|View full text |Cite
|
Sign up to set email alerts
|

Home management of childhood diarrhoea: Need to intensify campaign

Abstract: A review of home management of childhood diarrhea in under-five children among 203 Nigerian mothers was carried out over a period of 3 months in order to ascertain how effectively they manage their children with diarrhea outside a hospital setup (infrastructural health facility). Mothers whose children had diarrhea, with or without other symptoms, and presented at the Children's Out Patient unit (CHOP), of the UNTH over the study period were consecutively interviewed through a questionnaire designed for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 1 publication
8
22
6
1
Order By: Relevance
“…The high awareness (100% of mothers) of the use of ORS in the home management of diarrhoea reported in this study is similar to fi ndings noted in other studies 17,18,19 . In this study, 320 (88.88%) mothers had administered ORS to their children with diarrhoea prior to presenta on.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high awareness (100% of mothers) of the use of ORS in the home management of diarrhoea reported in this study is similar to fi ndings noted in other studies 17,18,19 . In this study, 320 (88.88%) mothers had administered ORS to their children with diarrhoea prior to presenta on.…”
Section: Discussionsupporting
confidence: 91%
“…A comprehensive study conducted in India demonstrated that 63% of Indian mothers were aware of ORS whereas only 27% of them took advantage of it for their children. 17 These studies suggest a profound lack between the cogni on of ORS and its u liza on. Thus, a superfi cial understanding of ORS is not enough and it requires consistent eff orts to emphasize on importance of ORS in resolving dehydra on during diarrhoea, par cularly in children; since this group of age is more likely to be dehydrated quickly 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge source of most mothers in the study were relatives and friends which was 76%, and almost 58% of them were informed by pediatric specialists (19). A comprehensive study conducted in India demonstrated that 63% of Indian mothers were aware of ORS whereas only 27% of them took advantage of it for their children (20). These studies suggest a profound lack between the cognition of ORS and its utilization.…”
Section: Discussionmentioning
confidence: 87%
“…2 The past gains of the prevention of dehydration from diarrhoeal disease have not been sustained, with studies documenting a decreased awareness of the use and proper constitution of Oral Rehydration Salts (ORS). 2,12,15 In a 2010 study in South East Nigeria, while 76% of the mothers knew they should use ORS for a child with diarrhoea, only 14.2% of them could correctly prepare ORS. [15] This decreased awareness and knowledge will obviously negatively impact on the disease outcome and may be partly why diarrhoeal mortalities are soaring.…”
Section: Discussionmentioning
confidence: 99%
“…2,12,15 In a 2010 study in South East Nigeria, while 76% of the mothers knew they should use ORS for a child with diarrhoea, only 14.2% of them could correctly prepare ORS. [15] This decreased awareness and knowledge will obviously negatively impact on the disease outcome and may be partly why diarrhoeal mortalities are soaring. Even though the mothers in our study were not questioned on their knowledge of oral rehydration, the proportion of our patients presenting with moderate and severe dehydration and shock (over 68%), with significantly increasing mortality based on severity of dehydration is highly suggestive of ignorance on the caregivers' part.…”
Section: Discussionmentioning
confidence: 99%